ARRHYTHMOGENIC CARDIOMYOPATHY OF THE RIGHT VENTRICLE COMORBID WITH HEMODYNAMICALLY SIGNIFICANT SECONDARY INTERATRIAL SEPTAL DEFECT - A. N. Shapieva; E. V. Zaklyazminskaya; Yu. V. Frolova; M. A. Nechaenko; A. G. Shestak; S. L. Dzemeshkevich (Российский кардиологический журнал, 2014)
Congenital atrial septal defect (ASD) is a common heart defect. The subjects for differential diagnosis of atrial septal defect, also leading to morpho-functional disturbances in the right parts of the heart, must be either inherited or acquired diseases. One such disease is arrhythmogenic right ventricular cardiomyopathy (ARVC), which leads to higher risk of sudden cardiac death (SCD) in young people. In the article we present the case of the patient with congenital heart disease: atrial septal defect operated at the age of 19. Deterioration of the condition was interpreted as a consequence of atrial septal defect. During examination at Russian scientific centre of surgery named after B.V. Petrovsky an independent hereditary disease — ARVC was dignosed. The disease was confirmed by molecular-genetic testing methods. A novel mutation in the gene p.S194L DSG2 homozygous was identified. On the basis of ARVC diagnosed on the base of physical, instrumental and genetic testing, the decision was made to implant a dual-chamber frequency adaptive cardioverter-defibrillator (ICD) for the prevention of SCD risk. The further tactics of patient monitoring must include not only regular ECG, echocardiogram, ICD function testing, but also cascade screening mutations responsible for the development of the ARVC in family members.